Feasibility study on the use of CMOS sensors as detectors in radioguided surgery with β−- emitters. (November 2020) - Alunni Solestizi, L.; Amoruso, R.; Biasini, M.; Bocci, V.; Campeggi, C.; Capotosti, A.; Collamati, F.; Faccini, R.; Kanxheri, K.; Mancini Terracciano, C.; Mantini, S.; Marafini, M.; et al.
Abstract: Radioguided surgery (RGS) is a medical practice which thanks to a radiopharmaceutical tracer and a probe allows the surgeon to identify tumor residuals up to a millimetric resolution in real-time. The employment of β − emitters, instead of γ or β +, reduces background from healthy tissues, administered activity to the patient, and medical exposure. In a previous work the possibility of using a CMOS Imager (Aptina MT9V011), initially designed for visible light imaging, to detect β − from 90 Y or 90 Sr sources has been established. Because of its possible application as counting probe in RGS, the performances of MT9V011 in clinical-like conditions were studied. 1 Through horizontal scans on a collimated 90 Sr source of different sizes (1, 3, 5, 7 mm), we have determined relationships between scan fit parameters and the source dimension, namely A quadratic correlation and a linear dependency of, respectively, signal integrated over scan interval, and maximum signal against source diameter, are determined. Horizontal scan measurements on a source, interposing collimators of different size, aim to determine relationships or correlations between scan fit parameters and source dimension. A quadratic correlation and a linear dependency of, respectively, signal integrated over scan interval, and maximum signal against source diameter are determined. In order to get closer to clinical conditions, agar–agar phantoms containing 90 Y with different dimensions and activities were prepared. A 90 Y phantom is characterized by a central spot and a ring all around, for simulating both signal (tumor) and background (surrounding healthy tissue). The relationship found between scan maximum and 90 S r source diameter is then exploited to extract the concentration ratio between spot and external ring of the 90 Y phantom. This observable, defined as the ratio between the tumor and the nearby healthy tissues uptake simulates the Tumor-to-Non-tumor Ratio (TNR). With the aim of evaluating the sensor's ability to discriminate signal from background relying on the significance parameter, a further 90 Y phantom, featuring a well-known and clinical-like activity will mimic the signal only condition. This result is used to extrapolate to different source sizes, after having estimated the background for various TNR. The obtained significance values suggest that the MT9V011 sensor is capable of distinguishing a signal from an estimated background, depending on the interplay among TNR, acquisition time and tumor diameter. Highlights: A CMOS imager has been used as sensor for beta- emission from isotopes ( 90 Y ) of interest in Radioguided surgery. Using a position scan a correlation between the source dimension and the shape of the response has been found. The sensitivity of the sensor to tumor detection has been determined by studying the interplay among TNR, acquisition time and tumor diameter.